Predictors of Early Outcome in Patients Admitted at the Emergency Department with Traumatic Brain Injury: a Retrospective Cross-Sectional Study - Muhammad Aslam Shaikh, Irfanullah Shah, Khalid Mehmood (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: The purpose of this study was to determine the factors that help predict early mortality in patients in the emergency department that have suffered a severe traumatic brain injury. Study design: A retrospective cross-sectional study Place and duration: Chandka Medical College/ Civil Hospital Larkana. April 2018- March 2020 Methodology: Retrospective analysis was used to study 198 patients that were admitted to the emergency department due to severe traumatic brain injury. The radiological, clinical, basic demographical, and biological data were all recorded when the patient was first admitted and while they were staying in the emergency department. Results: The results showed that 42 patients died. According to the univariate analysis, the presence of low value of Glasgow coma scale, bilateral mydriasis, shock, the high value of injury severity score, and cardiac arrest played a major role in the deaths of such patients. Poor outcome was associated with cerebral hematoma, subdural hematoma, and meningeal hemorrhage. A link was seen between poor prognosis and cardiac arrest and cerebral hematoma. Conclusions: In our study, subdural hematoma, intracranial hematoma, and meningeal hemorrhage were associated with mortality. To improve the prognosis of severe traumatic brain injury, prehospital care has to be improved. Additionally, futile resuscitations should be avoided. It is also very important to take a CT scan of the head as urgently as possible to detect operable mass lesions. Keywords: traumatic brain injury, early outcome, emergency department